2017
DOI: 10.1186/s12986-017-0173-7
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training to improve type 2 diabetes: working toward a prescription for the future

Abstract: The prevalence of type 2 diabetes (T2D) is rapidly increasing, and effective strategies to manage and prevent this disease are urgently needed. Resistance training (RT) promotes health benefits through increased skeletal muscle mass and qualitative adaptations, such as enhanced glucose transport and mitochondrial oxidative capacity. In particular, mitochondrial adaptations triggered by RT provide evidence for this type of exercise as a feasible lifestyle recommendation to combat T2D, a disease typically charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 92 publications
3
55
0
4
Order By: Relevance
“…These benefits are multifactorial, and some of them can be achieved through an increase in muscle mass (resulting in an improved glycemic control and increased resting energy expenditure and metabolic demand), but others are muscle mass-independent such as improvements in insulin action, enhanced postexercise oxygen consumption, increased mitochondrial content (increases the fatty acid oxidation capacity), or improved glucose homeostasis. 34 All these metabolic and molecular adaptations, along with the vascular adaptations with enhanced local muscular oxygen supply through capillarization, could be among the physiological mechanisms that may explain increases in CRF through RT. 32 Previous studies suggested focussing efforts on increasing CRF to minimize cardiometabolic risk in young men 14 as muscular fitness was less significant.…”
Section: T a B L Ementioning
confidence: 99%
“…These benefits are multifactorial, and some of them can be achieved through an increase in muscle mass (resulting in an improved glycemic control and increased resting energy expenditure and metabolic demand), but others are muscle mass-independent such as improvements in insulin action, enhanced postexercise oxygen consumption, increased mitochondrial content (increases the fatty acid oxidation capacity), or improved glucose homeostasis. 34 All these metabolic and molecular adaptations, along with the vascular adaptations with enhanced local muscular oxygen supply through capillarization, could be among the physiological mechanisms that may explain increases in CRF through RT. 32 Previous studies suggested focussing efforts on increasing CRF to minimize cardiometabolic risk in young men 14 as muscular fitness was less significant.…”
Section: T a B L Ementioning
confidence: 99%
“…Combinations of nutrients are favorable for potentiating the satiating effects of foods without having to apply high concentrations of the individual ingredients in the food's formulation. The use of nonivamide, for example, in large amounts, is limited due to its pungency, [19] and excessively high-protein diets may pose long-term health risks to the kidneys, [52] whereas a common side effect of high arginine doses above 9 g d -1 is diarrhea. [53] In the present study, each active agent was applied in an amount that is unlikely to induce any adverse effects, and the combined application of nonivamide, arginine, and wheat protein hydrolysate can be hypothesized to be more effective than the individual compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of exercise, including aerobic, resistance, and stretching exercises, can be prescribed for diabetic patients. It has been shown that resistance training and aerobic exercise can increase insulin sensitivity and daily energy intake and improve quality of life (15,16). On the other hand, the positive effect of physical activity on the reduction of insulin resistance may be related to the change in the secretion of adipokines (17).…”
Section: Introductionmentioning
confidence: 99%